Long-Term Changes In Rainfall Under Climate Change In East Nusa Tenggara Province 1971-2020 - Wibowo, Ofana Tri; Afghani, Fadhli Aslama; Mashuri, Imawan; Asifin, Hasyid Agha Zuhairul (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2024)
The current climate change is when the Earth's temperature increases due to increased greenhouse gas concentrations. The increase in greenhouse gasses has the potential to change the global climate system, one of which can impact changes in rainfall patterns. As a result, changes occur in various aspects of the planet, especially the atmosphere's composition, which can affect life on Earth. This study aims to analyze the characteristics of rainfall changes in East Nusa Tenggara Province during the 1971-2020 period. The data used is ERA5 reanalysis data in the form of daily rainfall with a spatial resolution of 0.25° X 0.25° for 50 years in East Nusa Tenggara Province for the period 1971-2020. The results of the analysis show that rainfall in East Nusa Tenggara Province has decreased from 1971-2020, with monthly and seasonal averages per period. The highest average monthly rainfall occurred in period 1 (1971-2000), with an average value of 137,491 mm, while the lowest value occurred in period 3 (1991-2020), with an average value of 125,242 mm. The highest average seasonal rainfall occurred in period 1 (1971-2000) of the DJF season, with an average of 757.19 mm, while the lowest value occurred in period 3 (1991-2020) of the SON season, with an average of 143.69 mm.